2008
DOI: 10.1029/2007gl031810
|View full text |Cite
|
Sign up to set email alerts
|

Velocity contrast along the Calaveras fault from analysis of fault zone head waves generated by repeating earthquakes

Abstract: [1] We systematically investigate the velocity contrast along the Calaveras fault that ruptured during the 1984 Morgan Hill earthquake using fault zone head waves (FZHW) that refract along the fault interface. We stack waveforms in 353 sets of repeating clusters, and align the peaks or troughs of the direct P waves assuming rightlateral strike-slip focal mechanisms. The obtained velocity contrasts are 2 -3% and 12-14% NW and SE of station CCO, respectively. The FZHW and the fault plane outlined by the relocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…In comparison, only 1-3% velocity contrast is observed SE of the epicenter along the Jiegu segment. The obtained values of velocity contrast is similar with those observed along major plate boundary faults, ranging from 5% to 10% along the Parkfield section of the SAF (e.g., Ben-Zion and Malin, 1991; Zhao et al, 2010), 3-12% along the Calaveras Fault (e.g., Zhao and Peng, 2008), 3-8% along the Hayward Fault (e.g., Allam et al, 2014), and ∼6% along the NAF (e.g., Bulut et al, 2012). Wang et al (2013) conducted a tomographic inversion in the same region and found clear velocity contrasts extending to ∼10 km depth in the NW part of the rupture zone (i.e., Jielong segment).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In comparison, only 1-3% velocity contrast is observed SE of the epicenter along the Jiegu segment. The obtained values of velocity contrast is similar with those observed along major plate boundary faults, ranging from 5% to 10% along the Parkfield section of the SAF (e.g., Ben-Zion and Malin, 1991; Zhao et al, 2010), 3-12% along the Calaveras Fault (e.g., Zhao and Peng, 2008), 3-8% along the Hayward Fault (e.g., Allam et al, 2014), and ∼6% along the NAF (e.g., Bulut et al, 2012). Wang et al (2013) conducted a tomographic inversion in the same region and found clear velocity contrasts extending to ∼10 km depth in the NW part of the rupture zone (i.e., Jielong segment).…”
Section: Discussionsupporting
confidence: 65%
“…(1). As was done before (e.g., Zhao and Peng, 2008;Zhao et al, 2010;Allam et al, 2014), we fit two slopes depending on whether the events occurred to the NW or SE sides of the station. Using the average P -wave velocity of 5.5 km/s (e.g., Liu et al, 2012;Wang et al, 2013), we estimate velocity contrasts at station ys02 to be ∼7.65% and ∼5.13% for events that occurred to the NW and SE sides, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…McGuire & Ben-Zion 2005;Zhao et al 2010;Share & Ben-Zion 2016), the North Anatolian fault in Turkey (Bulut et al 2012;Najdahmadi et al 2016) and other faults (e.g. Hough et al 1994;Zhao & Peng 2008;Yang et al 2015). FZHW also have horizontal particle motion (HPM) with a significant fault-normal component, since they are radiated from the fault, in contrast to the particle motion of the direct P wave that points in the epicentre direction (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, measurements of such differential times and waveform modeling of head waves document 20 %-50 % of velocity contrast in the Bear Valley region of the SAF (McGuire and Ben-Zion 2005). Similarly, along-strike variation of velocity contrast along the Calaveras fault has also been suggested by modeling FZHW (Zhao and Peng 2008). In addition to inspecting waveforms directly, polarization analysis has been applied in automatically identifying FZHW (Allam et al 2014b).…”
Section: Fz Wavesmentioning
confidence: 99%